Assessing Nigerian Tertiary Institutions Students' Awareness of Entrepreneurship in Textile Design Education - Benjamin, Emidun Olugbenga; Funke, Akinnibosun Oluwatoyin; Abiodun, Adeloye Adebayo (NIU Journal of Social Sciences, 2023)
This research investigated the awareness of entrepreneurship in textile design education among students in Nigerian tertiary institutions. The discipline of textile design stands as a significant field where entrepreneurship can foster creativity, economic sustainability, and industry relevance. Employing a survey design approach, the study used questionnaires to assess the extent of students' awareness and their perceptions about entrepreneurship the textile design. The population for this research are textile design students in selected tertiary institutions in Southwest Nigeria. The sample size used is One hundred and forty-three (143). Random sampling technique was used for sampling the students in order to avoid bias in the sampling process. The data collected was analyzed quantitatively through descriptive analysis using frequency, percentage and mean score. The result of the research revealed that students are adequately aware about the entrepreneurial nature of textile design. It was recommended that tertiary institutions should foster collaborations with textile industry stakeholders and also organize workshops, seminars, and guest lectures featuring successful entrepreneurs from the textile industry. It was also recommended that tertiary institutions should engage with alumni who have pursued entrepreneurial paths after graduation. Keywords: Textile design, education, tertiary institution, awareness